Emotion Regulation Training on Irritability, Alexithymia, and Interpersonal Problems of Adolescents With Disruptive Mood Dysregulation Disorder - Masoumeh Falah Neudehi; Farnaz Rezaei; Ameneh Bozorgi Kazerooni; Zahra Ebadi (Gonabad University of Medical Sciences, 2023)
Background: Difficulty regulating emotion has been identified as a trans-diagnostic factor common to various psychiatric diagnoses and behavior problems. This study aims to implement emotion regulation training techniques on adolescents with a disruptive mood disorder, emphasizing the irritability, alexithymia, and interpersonal issues in adolescents with disruptive mood dysregulation disorder. Methods: This quasi-experimental research used a pre-test and post-test design on 30 disruptive mood disorders in Tehran City, Iran, from 2022 to 2023. The participants were selected via simple purposive sampling. They were randomly assigned to two 15-member groups (experimental and control). The intervention group received self-regulation training over two months through eight 90-min group therapy sessions, whereas the control group received no treatment. The data were collected using the Barratt impulsiveness scale (BIS-11), Toronto alexithymia scale (TAS-20), and the inventory of interpersonal problems short-version. The data were analyzed by the SPSS software, version 25, and the multivariate analysis of covariance. Results: As indicated by the results, a significant difference was detected between the groups in terms of irritability (F=26.45, P=0.001, η=0.695), alexithymia (F=38.91, P=0.001, η=0.781), and interpersonal problems (F=31.27, P=0.001, η=0.734). Moreover, according to the alexithymia's largest effect size (0.781), emotion regulation training had more effect on alexithymia. Conclusion: Based on the results, emotion regulation training can be implemented effectively in clinics and psychological treatment centers. Also, because of using emotion regulation training, it is possible to improve these people's psychological characteristics and social relations. It is also suggested that relevant organizations train specialists and school counselors accordingly.